Determination of 2, 6-Dichlorophenol by Surface-Enhanced Raman Scattering with Molecular Imprinting. (2nd September 2018) - Wang, Zirun; Li, Hongji; Wang, Xiaonan; Jiang, Jiaqi; Sun, Hanyang; Wang, Liang
ABSTRACT: A novel method has been reported for 2, 6-dichlorophenol using surface-enhanced Raman scattering (SERS). SiO2 /gold composites were selected as the SERS substrates to provide the response of gold nanoparticles. Molecular imprinting was subsequently used for the development of a specific detector to 2, 6-dichlorophenol with precipitation polymerization. The molecularly imprinted polymer provided sensitive and selective SERS detection for the determination of 2, 6-dichlorophenol. The intensity and concentration obeyed a linear relationship from 1 × 10 −5 to 1 × 10 −9  mol L −1 2, 6-dichlorophenol. The sensitivity of SERS with the molecularly imprinted polymers provides a promising approach for practical analysis.